Megafauna mobility: Assessing the foraging range of an extinct macropodid from central eastern Queensland, Australia - Christopher Laurikainen Gaete; Anthony Dosseto; Lee Arnold; Martina Demuro; Richard Lewis; Scott Hocknull (PLoS ONE, 2025)
Understanding the factors that influence the geographic range of extinct megafaunal species is crucial for reconstructing their ecology and extinction dynamics. For extant herbivores, it has been demonstrated that large body mass provides the potential for greater geographic range. Allometric scaling relationships are observed in placental mammals but have not been well-established for marsupials, in particular, extinct marsupial megafauna. Here, we employ a phylogenetic generalised least squares regression model using extant macropodids to estimate home ranges for individuals from the extinct genus Protemnodon. The regression model predicts a mean home range of 11.6 ±  5.8 km2 This prediction, centred on Mt Etna caves, incorporates several distinct geological features with variable, known 87Sr/86Sr isotope ratios. Fossil Protemnodon individuals recovered from cave deposits at Mt Etna returned 87Sr/86Sr values similar to that of the host limestone, in which the cave systems formed, and the broader Mount Alma Formation. This similarity suggests that individuals foraged close to where they were fossilised, indicating a smaller home range than predicted. Smaller home ranges for individuals with a large body-mass were unexpected, attributed to a unique combination of individual behaviour, diet and/or locomotion regime within stable rainforest environments. Our results suggest that, foraging ranges in marsupial megaherbivores may be more strongly associated with environmental quality rather than body mass. New in-situ uranium-thorium and single-grain TT-OSL ages refine, and are in agreement with, previous interpretations of chronology, indicating that rainforest-adapted fauna persisted at Mt Etna until at least 280 ka. We propose that small home ranges in a stable environment, such as rainforests, predisposed these megafauna macropodids to extinction after 280ka, driven by an increasingly dry and unstable climate. Our results underscore the need for regionally specific biologies of individuals, populations and species when considering extinction pathways for Pleistocene fauna.